Pengaruh Pemberian Ischemic Compression Technique Terhadap Penurunan Nyeri Myofascial Trigger Point Syndrome Otot Upper Trapezius Pada Pegawai Manejerial RS UMM - Lutfi Ardi Firmansyah; Achmad Fariz; Rachma Putri Kasimbara; Yohanes Deo Fau (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Â The Ischemic CompressionApproach is a safe and effective technique for pain relief in myofascial conditions. The purpose of assessing the effect of Ischemic CompressionTechnique on reducing Myofascial Trigger Point Syndrome Upper Trapezius muscle pain in UMM Hospital managerial staffMethods: Â This study is classified as a comparative quantitative study, including statistical data processing by comparing or looking for differences between before and after therapy. The population in this study were managerial employees of UMM Hospital with complaints of neck pain in the last 1 month of the July 2022 period at UMM Hospital with a total sample of 30 respondents using Wilcoxon Test data analysisResults: Â The results of the analysis showed that the significance value of the Wilcoxon Test was 0.000 <Î± (Î± = 0.05), meaning that there was an effect of Ischemic CompressionTechnique on reducing Myofascial Trigger Point Syndrome pain in the Upper Trapezius muscle in managerial employees of UMM HospitalConclusion: 1) The value of pain before administration of the Ischemic CompressionTechnique obtained an average value of 1.37 with a minimum value of 1 and a maximum value of 2 and a standard deviation value of 0.490 2) The value of pain after administration of the Ischemic CompressionTechnique obtained an average value of 0.40 with a minimum value of 0 and a maximum value of 1 and a standard deviation value of 0.498 3) There is an effect of Ischemic CompressionTechnique on reducing Myofascial Trigger Point Syndrome Upper Trapezius muscle pain in managerial staff of UMM Hospital